Effects of sweet pepper straw biochar on soil microbial communities and growth of continuously cropped cucumber - Hengyu Li; Jie Lou; Xiaolu Chen; Yuwei Dou; Dalong Zhang; Min Wei (Annals of Microbiology, 2024)
Abstract Purpose This study evaluates biochar from crop residues as a solution to soil degradation in continuous monoculture within greenhouse agriculture, focusing on its impact on soil microbial communities and cucumber plant growth. Methods We analyzed biochar derived from tomato straw (TSB), sweet pepper straw (SPSB), and eggplant straw (ESB), assessing their nutrient content, cation exchange capacity, and adsorption rates. This study examined the effects of three concentrations (2.5%, 5%, and 7.5% w/w) of the more promising SPSB on soil properties and cucumber growth. Results SPSB showed significantly higher levels of nitrogen, phosphorus, and potassium, along with superior adsorption capacity compared to TSB and ESB. The 5% w/w SPSB concentration notably improved cucumber growth, increasing plant height by 13.01%, stem thickness by 20.79%, leaf area by 50.26%, and dry weight by 58.56% relative to the control. High-throughput sequencing revealed this concentration significantly altered soil microbial community structure, enhancing bacterial and fungal diversity. It increased beneficial bacterial groups (Firmicutes, Actinobacteria, Bacillus) and modified fungal communities, with a decrease in Ascomycota and Aspergillus and shifts in Penicillium abundance. Functional genomic analysis indicated enrichment in bacterial metabolic pathways and fungal replication and expression genes. Conclusion SPSB, especially at a 5% w/w concentration, emerges as an effective soil amendment in greenhouses affected by continuous monoculture. This approach represents a sustainable method to enhance soil health and crop productivity.